A transparent electrode with water-oxidizing activity. (20th December 2018) - Azadi, Gouhar; Bagheri, Robabeh; Bikas, Rahman; Mousazade, Younes; Cui, Junfeng; Song, Zhenlun; Kinzhybalo, Vasyl; Shen, Jian-Ren; Allakhverdiev, Suleyman I.; Najafpour, Mohammad Mahdi
Abstract: Hydrogen production by water splitting is a promising method to store energy. Water-oxidation reaction is a bottleneck in water-splitting systems. Herein, a mononuclear nickel(II) phosphine complex with 1, 2-bis(dicyclohexylphosphino)ethane ligand, was synthesized and characterized by X-ray crystallography method. The water-oxidizing catalyst under the electrochemical condition was studied. The role of Ni compound for the water-oxidation reaction on the surface of fluorine-doped tin oxide as one of the true catalysts was investigated by the electrochemical methods and Scanning Electron Microscopy coupled with Energy Dispersive X-ray (SEM/EDX) Spectroscopy. The big ligand around the Ni ion causes a very small size of Ni-based particles on the surface of the electrode, which are the active catalysts for the water-oxidation reaction. Such small nanosized Ni-based compounds are transparent and have no effect on the transparency of the obtained fluorine-doped tin oxide. Thus, it is a promising method to synthesize a transparent fluorine-doped tin oxide with water-oxidizing activity. Highlights: Hydrogen production by water splitting is a promising method to store energy. A mononuclear nickel(II) phosphine complex was synthesized and characterized. The complex formed a Ni-based compound on the obtained fluorine-doped tin oxide. A transparent electrode with water-oxidizing activity was reported.